A Dual Path Model of Work-Related Well-Being in Healthcare and Social Work Settings: The Interweaving Between Trait Emotional Intelligence, End-User Job Demands, Coworkers Related Job Resources, Burnout, and Work Engagement - Tesi, Alessio (Frontiers in Psychology, 2021)
Framing the job demands-resources (JD-R) model, we studied how trait emotional intelligence (TEI, i.e., perception about one’s own emotional realm) contributes to the work-related well-being of healthcare professionals. A total of 302 healthcare professionals were involved in the study and completed an anonymous self-report questionnaire. The results of the structural equation modelling revealed that TEI was directly and indirectly—mediated by end-user job demands—negatively associated with burnout, and directly and indirectly—mediated by coworkers related job resources— associated with work engagement. According to the health impairment and motivational processes of JD-R, we found that TEI targets burnout and work engagement through different paths. The first path revealed that TEI would reduce burnout protecting by the insurgence harmful relationships with service end-users and the second showed that TEI would promote work engagement sustaining the development of positive relationship with coworkers.